A preliminary analysis of Bidayuh Jagoi Patun - Fatimah, Hj Subet; Shanthi, Nadarajan; Dayang Sariah, Abang Suhai (Issues in Language Studies, 2013)
Bidayuh Pantun or Patun remains a under researched topic in Borneo studies and language research due to the difficulties associated with obtaining critical, poetic information in oral culture, language variations and societal mobility. Existing data from anthologies however provide little detail about the instrinsic and extrinsic features ascribed to the poem by the people who produce and use them. This paper attempts to explore patun from the Jagoi community. In this study, the structural aspects, themes and moral values of 47 patun from the Jagoi community were analysed. The initial explanations suggested by the poet were further analysed to determine the various structural features to place it alongside existing mainstream lyric poetry. The analysis of the intrinsic features showed that good rhythmic patun has four to six words per line and eight to 12 syllables per line, and the final syllables of each line has assonance and consonance patterns of a-a-a-a and a-b-a-b. The themes of the patun include love, advice, forgiveness, beliefs, hopelessness and happiness, and the moral values take the form of subtle advice and admonishments. The Bidayuh patun is indeed a projection of knowledge, experiences, beliefs, values, and emotions of the community